The search for a method to unpack urban complexity: Case study of the City of Johannesburg - Laila R., Smith; Lewis, Ndhlovu; Stephen, Narsoo (African Evaluation Journal, 2017)
The City of Johannesburg (COJ) provides services to approximately 5 million people; yet the elements of monitoring and evaluation remain a missing link in the design and implementation of programmes. This was the case even after the introduction of the monitoring and evaluation framework in 2012. This case study is filling an empirical gap.
Keywords: The search for a method to unpack urban complexity